Transient spiral structure and the disc velocity substructure in Gaia DR2 - Hunt, Jason A. S.; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The second data release from ESA’s Gaia mission has revealed many ridge-like structures in the velocity distribution of the Milky Way. We show that t